Convalescent plasma treatment of critically ill intensive care COVID‐19 patients. Issue 5 (8th April 2021) - Lindemann, Monika; Lenz, Veronika; Knop, Dietmar; Klump, Hannes; Alt, Mira; Aufderhorst, Ulrich W.; Schipper, Leonie; Schwarzkopf, Sina; Meller, Lara; Steckel, Nina; Koldehoff, Michael; Heinold, Andreas; et al.
Abstract: Background: Infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) may be life‐threatening, and specific antiviral drugs are currently not available. However, first studies indicated that convalescent plasma treatment might improve the clinical outcome of coronavirus disease 2019 (COVID‐19) patients. Study Design and Methods: In the current study, we investigated the efficacy of convalescent plasma treatment in eight COVID‐19 patients. All the patients were critically ill, and seven of them were SARS‐CoV‐2 RNA–positive when starting treatment. SARS‐CoV‐2–specific antibodies were determined by an enzyme‐linked immunosorbent assay detecting immunoglobulin G (IgG) antibodies against the S1 protein (Euroimmun), and the neutralizing titers were determined with a cell‐culture‐based neutralization assay. Plasma treatment started between 4 and 23 days after the onset of symptoms. The patients were usually treated by three plasma units, each containing 200–280 ml, which was applied at day 1, 3, and 5. Results: Donor sera had on average lower IgG antibody ratios and neutralizing titers than the COVID‐19 patients before the onset of treatment (median ratio of 5.8 and neutralizing titer of 1:320 vs. 7.5 and 1:640, respectively). Nevertheless, we observed an increase of antibody ratios in seven and of neutralizing titers in five patients after treatment; which did, however, not correlate with patient survival. Plasma treatment was effective in three patients, but five deceased despite treatment. Patients who deceased had a later treatment onset than survivors and finally died from multiple organ failure. Conclusion: Our data indicate that the efficacy of convalescent plasma treatment of critically ill COVID‐19 patients who already had developed strong antiviral immune responses and organ complications is limited.